Uplift and denudation history of the Akaishi Range, a thrust block formed by arc‐arc collision in central Japan: Insights from low‐temperature thermochronometry and thermokinematic modeling. Issue 8 (14th August 2017) - Sueoka, S.; Ikeda, Y.; Kano, K.; Tsutsumi, H.; Tagami, T.; Kohn, B. P.; Hasebe, N.; Tamura, A.; Arai, S.; Shibata, K.
Abstract: Fission track (FT), (U‐Th)/He (He), and U‐Pb data were used to identify the denudation history of the Akaishi Range, central Japan. The northern Akaishi Range is bounded on the east by the Itoigawa‐Shizuoka Tectonic Line Fault Zone (ISTL‐FZ). The thermochronometric ages progressively decrease with the decreasing distance to the ISTL‐FZ. Thermokinematic calculations suggest that the age pattern observed can be explained by 5–7.5 mm/yr reverse slip on the ISTL‐FZ that dips 34–45° west and soles onto detachment at 20–22.5 km depth. By assuming the same geometry and slip rate of the fault, the bedrock uplift rates and denudation rates are estimated at ~4 mm/yr. Thus, the uplift and denudation style of the northern Akaishi Range is well explained as a simple tilted thrust block that has been exhumed along the listric ISTL‐FZ. On the other hand, considering both the difference in apatite FT age and the active fault distribution, the southern Akaishi Range might be different in uplift origin and timing, although the difference in apatite FT ages between them may be attributable to the chlorine content variation in apatite. The inferred total denudation is larger than several kilometers and likely exceeds 10 km since the beginning of the northern Akaishi Range uplift, suggesting that the low‐relief surfaces on the ridges and the relatively constant elevations of the summits reflect postuplift denudation rather than preexisting low‐relief landforms. Key Points: Thermochronometry revealed that thrusting uplifts the northern Akaishi Range Geometry and slip rate of the thrust are estimated by thermokinematic modeling Different uplift processes were suggested in the northern and southern Akaishi Ranges